Objektive Maße bei der Anpassung der Prozessoren von Cochleaimplantatsystemen: Nutzung von Diskriminationsfunktionen und Betrachtung von Elektrodenprofilen = Objective measures for setting the processors of cochlear implant systems : use of discrimination functions and consideration of electrode profiles - Hoth, Sebastian; Brill, Ioana; Praetorius, Mark (HNO, 2016)
BackgroundWhen setting the electrical stimulation level of cochlear implants during individual adjustment of the speech processor, especially in children, objective measures such as intracochlearly measured electrically evoked compound action potentials (eCAP) and intraoperative observation of electrically elicited stapedial reflexes (eSR) are indispensable. The benefit of these objective measures is based on the correlation between the derived response thresholds and psychometric data.Materials and methodsThe amplitude growth functions of eCAPs were measured intraoperatively for all electrodes in 30 ears of adult patients. The stimulus-dependent incidence of observable eSRs was recorded for all electrodes in 16 ears of adult patients. For evaluation of the data, new algorithms were applied which allowed the determination of thresholds without intervention of the investigator. Essential features were the conversion of observations into binary variables, and the consideration of logistic discrimination functions and their exceedance of a numeric threshold criterion.ResultsRegarding the eCAP data, closer and significant correlations are observed between objective thresholds and psychometric measures in comparison to conventional procedures. Profiles are more efficient than pooled data. Significant correlations are also observed for eSR thresholds, albeit to a lesser extent and without an evident difference between profiles and pooled data.ConclusionConsidering the by no means consistent international literature, the results illustrate the need for a consistent definition of response thresholds and the consideration of electrode profiles.
Gesehen am 18.08.2017